Efficiency of Mass Rapid Transit (MRT) among selected ASEAN Countries using Data Envelopment Analysis (DEA) approach / Farah Mardhiyah Mohd Isa and Nor Farihah Nor Azman - Mohd Isa, Farah Mardhiyah; Nor Azman, Nor Farihah (2021)
This paper provides a comprehensive overview of Mass Rapid Transit (MRT) efﬁciency in selected ASEAN countries that includes Malaysia, Philippines, Thailand, Singapore, and Indonesia. MRT is one of the popular railway public transport that has become people’s alternative to move freely. However, inadequate study of MRT produces the question of whether this development is efﬁcient or inefﬁcient. Using Data Envelopment Analysis (DEA) to measure efﬁciency, this method can also identify the ways to make improvements to increase the efﬁciency of the MRT of ASEAN countries that are inefﬁcient. Data obtained from the Ministry of Transport of each respective country were analyzed using Data Envelopment Analysis Online Software (DEAOS). The study identiﬁes the efﬁciency score for CCR (Charnes, Cooper, Rhodes) and BCC (Banker, Charnes, Cooper) models for both input- and output-oriented. The analysis showed different results for CCR and BCC models. CCR model indicated that only Philippines and Singapore are efﬁcient while BCC model indicated that Indonesia, Philippines and Singapore are efﬁcient. The improvement made for inefﬁcient decision making units (DMUs) only focus on BCC output-oriented model as it is more reliable to the real world since the reality have several constraints. The study reveals that inefﬁcient DMUs which are Malaysia and Thailand must increase the number of passengers by 199.57% and 80.69% respectively to increase efﬁciency. The ﬁndings of this study beneﬁts the decision-makers in order to measure the smoothness operations of MRT using inputs and output obtained.